Emergence of New Regionalism in South Asia - Mohd Wani, Gull (International Journal of Psychosocial Rehabilitation, 2020)
Regionalism in South Asia has different meanings than what is meant by it in other regions like the European Union, African Union, Organization of American States, etc., because South Asia is prone to many problems, be it terrorism, insecurity, poverty, diseases, etc. besides this, there is mistrust and misunderstanding between and among countries of south Asia particularly India and Pakistan which prevented the region from making any organization that could remove the conflicts between them. The SAARC is concrete example, as it is in great trouble, so now south Asia is looking for alternative regional and regional organizations like become the member of BIMSTEC so to look towards Southeast Asia and improve their relations by trying to develop common market outside its south Asian region that could upgrade their trade and, all in all, their relations with the neighbors. India also joined BBIN, consider it as economic corridor which will develop the northeastern states of India. By this corridor, transfer of goods and services between the member countries will take place,. In this paper we will discuss problems of SAARC and new regional organizations of south Asia and their impact on the region